Accuracy of Perineal Percutaneous Fine Needle Aspiration Cytology (FNAC) of Prostate under Ultra- Sound in Comparism with Transrectal Aspiration in Diagnosis of Prostatic Cancer - Aljebori, Hussain Abady (Iraqi Journal of Cancer and Medical Genetics, 2017)
Background: Prostatic carcinoma is the commonest internal malignancy of adult males. Patients usually presenting with voiding symptoms. Clinical suspicion of prostatic carcinoma depends on finding of one or more of the followings; hard prostatic nodule(s) on digital rectal examination (DRE), hypoechoic lesion on transrectal ultrasonography (TRUS), and/or high serum level of prostatic specific antigen (PSA). Final diagnosis depends on FNAC and/or histopathology. Objective: This is a case control prospective study designed to evaluate the usefulness of FNAC of prostate through perineal skin under ultrasound instead of transrectal aspiration in diagnosis of suspicious prostatic conditions. Patients and Methods: One hundred and ten males with voiding symptoms and clinical suspicion of prostatic carcinoma were participated in the study. Their ages were between 45 and 92 years. The aspiration was carried out as outpatient procedure. Results: Cytopathological results were; 64 (58.18%) positive, 4 (3.64%) suspicious, and 40 (36.36%) negative for prostatic cancer. Two specimens (1.82%) were inadequate for proper cytopathology. Results of histopathological examination of resected specimens from the same patients was very close to that of cytopathology with only two false positive and one false negative results. There was no any mentioned complication following aspiration, and sensitivity, specificity, and accuracy were 98%, 95%, and 91.81% respectively, and all results were statistically significant with p-values <0.05. Conclusion: Percutaneous perineal FNAC of prostate under ultrasound is a safe, reliable, cost effective, and as accurate as transrectal FNAC in diagnosis of prostatic cancer. Keywords: Perineal prostatic FNAC, Prostatic Cytopathology, PSA, TRUS.